Improved High-Level Synthesis for Complex CellML Models - Liebig, Björn; Oppermann, Julian; Sinnen, Oliver; Koch, Andreas (Applied Reconfigurable Computing. Architectures, Tools, and Applications, 2018)
In this work, we present the use of a new high-level synthesis engine capable of generating resource-shared compute accelerators, even from very complex double-precision codes, for cell biology simulations. From the domain-specific CellML description, the compilation pipeline is able to generate hardware that is shown to achieve a performance similar to or exceeding current generation desktop CPUs, and has energy savings of up to 96% even for a single accelerator, which requires just 25–30% area on a mid-sized FPGA.